Investigation of disorders of the anorectum and colon. - Henry, M. M. (Royal College of Surgeons of England, 1985)
Previously, investigation of disorders of the anorectum and colon have been limited to manometric, external anal sphincter muscle electromyographic and contrast radiological techniques. In this paper we describe other investigative techniques recently developed at St. Mark's Hospital, London and their application in the investigation of certain disorders of the anorectum and colon.